THERAPY OF ENDOCRINE DISEASE: Medical treatment of primary aldosteronism. Issue 4 (October 2019) - Lechner, Benjamin; Lechner, Katharina; Heinrich, Daniel; Adolf, Christian; Holler, Finn; Schneider, Holger; Beuschlein, Felix; Reincke, Martin
Abstract : In patients with primary aldosteronism, specific treatment provides prognostic benefit over optimal antihypertensive therapy and is therefore crucial to reduce mortality and morbidity in this subgroup of patients with hypertension. Prognostic relevance has been shown for adrenalectomy in unilateral disease and for medical treatment with mineralocorticoid receptor antagonists in bilateral adrenal hyperplasia. Collectively, evidence points to the superiority of surgical treatment compared to medical treatment. The causal approach of removing the mineralocorticoid excess, as well as the often-accompanying glucocorticoid excess, might provide one biologically plausible explanation for the observation of slightly better outcomes with surgical therapy. However, in patients living with primary aldosteronism, medical treatment is often insufficient for three major reasons. First and foremost, no marker of sufficient aldosterone blockade has yet been established and therefore adequate treatment of the aldosterone excess is often dismissed as a treatment goal. Second, side effects often limit patient compliance. Third, as recommendations differ from other indications like heart failure, drug dosing is often inadequate. The aim of this review is first to provide an overview over medical treatment options and second to review potential markers for treatment surveillance in patients with primary aldosteronism.